UPAYA MENINGKATKAN KEMAMPUAN MENULIS SURAT PRIBADI DENGAN MENGGUNAKAN TEKNIK PEMODELAN SISWA KELAS V SD KARYA THAYYIBAH MAMBORO - Ifriana, Ifriana (BAHASANTODEA, 2015)
The research problems were (1) how was the improving increase in the ability to write a personal letter using modeling techniques of the fifth grade students work at SD Tayyibah Mamboro Palu (2) how was the result of improvement in the ability of personal letter by using modeling techniques of the fifth grade students work at SD Tayyibah Mamboro Palu. The objectiveof this resrsearh was to describe the increase in the ability to write a personal letter using modeling techniques of the fifth grade students work at SD Tayyibah Mamboro Palu and describe the results of an increase in the ability to write a personal letter using techniques of the fifth grade students work at SD Tayyibah Mamboro Palu. This research used qualitative approach and the type of research was a classroom action research. Data collected by observation, interviews, and documentation. Based on the research findings, it was showed that the use modeling techniques could improve the ability of students to write a personal letter. It was found out an increase in the number of students who have chieved the criteria of succes from the first cycle to the second cycle. Furthermore, there were an increase in the value average of writing a personal letter from the first cycle to the second cycle. In the pre-cyle stage, only 23% of students who achieved mastery learning, whereas in the first cycle after the implementation of modeling techniques as 54% of students who completed the criteria of succes, it was indicated that the learning outcomes have increased by 31%. Moreover, in the second cycle the students who have completed was 77% indicated that the number of students who achieve the criteria of succes increased to 10 from 13 students. Classically, the percentage between the first cycle and second cycle increased into 23 23%.          Keywords: Writing, Personal Letters, Modeling Techniques.